2012
DOI: 10.1021/la302110a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carboxymethyl Cellulose on Polymer Surfaces: Evidence of a Specific Interaction with Cellulose

Abstract: The adsorption of carboxymethyl cellulose (CMC), one of the most important cellulose derivatives, is crucial for many scientific investigations and industrial applications. Especially for surface modifications and functionalization of materials, the polymer is of interest. The adsorption properties of CMC are dependent not only on the solutions state, which can be influenced by the pH, temperature, and electrolyte concentration, but also on the chemical composition of the adsorbents. We therefore performed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 45 publications
10
53
0
Order By: Relevance
“…Subsequently it has been shown that addition of calcium chloride or other salts can facilitate the adsorption of the anionic CMC onto generally anionic cellulosic surfaces Duker and Lindström 2008;Liu et al 2011b). Evidence of a special affinity between CMC and pure cellulose surfaces was shown by Kargl et al (2012), who attributed the favorable adsorption to chemical similarity. It was suggested by Laine et al (2000) that the effect can be attributed to a form of co-crystallization between the flexible CMC macromolecules and the partially crystalline cellulose surfaces to which they are adsorbed.…”
Section: Treatment Of Papermaking Fibers With Carboxymethylcellulose mentioning
confidence: 99%
“…Subsequently it has been shown that addition of calcium chloride or other salts can facilitate the adsorption of the anionic CMC onto generally anionic cellulosic surfaces Duker and Lindström 2008;Liu et al 2011b). Evidence of a special affinity between CMC and pure cellulose surfaces was shown by Kargl et al (2012), who attributed the favorable adsorption to chemical similarity. It was suggested by Laine et al (2000) that the effect can be attributed to a form of co-crystallization between the flexible CMC macromolecules and the partially crystalline cellulose surfaces to which they are adsorbed.…”
Section: Treatment Of Papermaking Fibers With Carboxymethylcellulose mentioning
confidence: 99%
“…Physical adsorptions are usually weak and reversible. However, the adsorption of carboxymethyl cellulose (CMC) onto cellulose surfaces is generally specific and irreversible, (Kargl et al 2012), and thus CMC is widely used as anchoring layers on cellulose surfaces for further modifications Mohan et al 2014;Orelma et al 2011;Orelma et al 2012b;Orelma et al 2012c). Covalent modification can be realized via Bgraft onto^and Bgraft from^approaches.…”
Section: General Methodologymentioning
confidence: 99%
“…This result is in accordance with the report published by Kargl et al, where a reduced water contact angle is noted for hydrophobic polymeric surfaces (e.g., cellulose acetate and cyclo olefin polymer) that are coated with hydrophilic CMC molecules. 29 For the covalent immobilization with method III, exceptionally high enzymatic activities are observed (on BCMC: HRP 1 g L −1 , ABTS: 0.055 U, Δf 3 = −133 Hz, ΔD 3 = 11.9 × 10 −6 ). When these values are compared with method II on BCMC, one can see that QCM-D frequency shifts and ABTS activity correlate well.…”
Section: Biomacromoleculesmentioning
confidence: 99%